Internal mammary artery perforators as recipient vessels for free tissue transfer in head and neck reconstruction: A case report and literature review. Issue 4 (7th November 2020) - Scaglioni, Mario F.; Meroni, Matteo; Fritsche, Elmar; Rajan, Gunesh
Abstract: Head and neck defect reconstruction is a common challenge for plastic surgeons. Microsurgical free tissue transfer is a frequently used solution but its success strictly depends on the quality of recipient vessels. A particularly demanding situation occurs when there are no nearby available vessels because of previous extensive neck dissection and radiotherapy. In similar cases, it is necessary to resort to other and farther vessels. Common alternatives might be the thoraco‐acromial vessels, the transverse cervical vessels, and the internal mammary vessel. Recently, the perforator vessels of the internal mammary artery and vein were shown to be safe alternatives as recipient vessels for autologous breast reconstruction, causing less morbidity and allowing adequate perfusion of rather large flaps. Here we present a floor of the mouth reconstruction after cancer relapse resection. In this case, we employed a chimeric anterolateral thigh (ALT) free flap anastomosed to the internal mammary perforator vessels in end‐to‐end fashion. A 46‐years‐old male patient presented a defect in the floor of the mouth and base of the tongue after cancer removal. No nearby vessels were available because of extensive fibrosis and damages due to previous surgeries and radiotherapy. Therefore, on the basis of our experience in autologous breast reconstruction, we chose the internal mammary perforator vessels in the recipient side and we harvested a chimeric ALT‐based skin island then split into two parts for mouth reconstruction and monitoring. We performed the anastomosis resorting to internal mammary perforator vessels and we obtained a satisfactory result from both the functional and aesthetic point of view. Postoperative course was uneventful and at 6 months follow up the reconstructive result was good with no functional issue. We believe that this might be a valid and modern evolution of the use of internal mammary vessels as recipient vessels and that it is a worthy addition in the field of perforator‐anastomosed flaps, extending its application also to head and neck reconstructions. Moreover, a brief literature review about alternative recipient vessels for depleted neck is also provided.